基于ANSYS/LS-DYNA的转炉倾动装置齿轮动态啮合分析 - 任学平; 孙百祎; 杨松涛 (Jixie Chuandong, 2014)
When detecting the equipment,the vibration signal of four reducers is gathered by using EZANALYST,it is found that one reducer action is hysteretic leading to the collision between two gear teeth.To investigate the influence of impact lead on gear strength under the collision situation,combining the theory of contact dynamics and using the ANSYS/LS-DYNA the working conditions of reducer pulse-on and braking stage are simulated.Through the finite element analysis,the position of maximum equivalent stress are consistent with the actual concentrated place.Through comparing the analysis results of pulse-on and braking stage,show that the impact load in the pulse-on stage is bigger owing to the larger backlash,therefore,the reducer asynchronous drive in the actual production process must be avoided.